Assessment on the use and availability of rice certified seeds in Bone regency, South Sulawesi province. (May 2018) - Farid, M; Iswoyo, H; Ridwan, I; Nasaruddin,; Dermawan, R
Abstract: Use of certified seeds is necessary in rice farming system to ensure high production and productivity. In South Sulawesi, as one of the main center of Rice in Indonesia, increase in the regional harvest areas and land productivity was not followed by significant increase in rice productivity. Seeds policy implemented by the government not only covers the technology applied in the seeds production but also quality insurance, availability and its distribution system. Despite these efforts, use of certified seeds in the field by farmers are still limited, therefore a survey was conducted to study the use and availability of rice certified seeds in Bone regency. Farmer groups in 9 districts were sampled to obtained data concerned to the use and availability of rice seeds including type, planting season, cropping pattern and availability at planting. Results show that the use of certified seeds in Bone regency were relatively high, however level of seeds supply was low or delayed at time of planting. To overcome the problem of seed supply, most farmers used its own seeds from previous harvest. Some suggestions to resolve this condition are discussed.